A Rare Case of Intestinal Obstruction from Internal Hernia through a Foramen Formed by Appendices Epiploicae – A Case Report and Review of Literature - Olajide, Thomas Olagboyega; Balogun, Olanrewaju (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Internal hernias are uncommon causes of acute abdomen and intestinal obstruction. Internal herniation due to appendices epiploicae is very rare with only six cases reported in the literature. CASE REPORT: We, herein, present the report of a 64-year-old female who presented with features of intestinal obstruction due to internal herniation of a loop of small intestine through an orifice formed by the fusion of two appendices epiploicae. The band was divided into release the entrapped loop of bowel. CONCLUSION: A high index of suspicion with prompt surgical intervention will improve outcome.